Salivary Cortisol Measurement Contamination After Oral Hydrocortisone: A Randomized Crossover Trial - Chihaoui, Melika; Mouelhi, Yasmine; Hammami, Bessem; Oueslati, Ibtissem; Khessairi, Nadia; Chaker, Fatma; Yazidi, Meriem; Feki, Moncef (Hormone and Metabolic Research, 2024)
The study aimed to evaluate salivary cortisol (SC) contamination and determine the associated factors in secondary adrenal insufficiency (SAI) patients treated with hydrocortisone (Hc). A randomized crossover trial involved SAI patients. SC was measured before the morning Hc dose, then at one, two, and four hours after. The procedure was performed twice on two days of a week: one day while taking Hc in tablet form (tablet set) and one day while taking Hc in capsule form (capsule set). Area under the curve (AUC) of SC levels over time was calculated in each participant for the two sets. SC contamination was defined as AUCtablet above the 95th percentile of AUCcapsule. Thirty-four patients (24 females and 10 males) with a median age of 48 years were enrolled. Post-Hc dose SC levels were higher in tablet than in capsule set, particularly at one hour. Prevalence and extent of SC contamination were estimated to 32% and 88%, respectively. In capsule set, SC measured two hours after Hc intake showed the strongest correlation with AUC (r=0.88, p<0.001). In multivariate analysis, serum potassium≥3.9 mEq/l was the only predictor for SC contamination [multi-adjusted OR (95% CI): 7.1 (1.4–36.1); p=0.018]. SC measured during the two hours after Hc intake is inaccurate for glucocorticoid replacement therapy assessment in SAI patients treated with Hc in tablet form.
Keywords: salivary cortisol; adrenal insufficiency; hydrocortisone; biomarker; controlled clinical trial; diagnostic errors